Deconstruction of Werabur Lake Folktale From West Papua - Ananda, Citra Putri; Ekawati, Anita Dewi (UPA Bahasa Universitas Tidar And HISKI Kedu, 2023)
This study aims to describe deconstruction in the Werabur Lake folktale from West Papua. This research using content analysis method with deconstruction approach. Collection technique the data uses a document study with the data source of the Werabur Lake folktale from West Papua. Data collected by method reading folktale and taking notes on deconstruction. Data analysis techniques include several steps namely; establish research objectives, formulate data findings, tabulate and provision of coding, interpretation, and drawing conclusions. Test the validity of the data with using member check. The results of the research show that there is deconstruction which depicts that the grandmother who is told as a loving figure commits some cruel acts, such as violating customary rules on purpose to bring disaster, not telling people that disaster is coming, and making innocent people die as a result of disaster even though only one person is guilty.